SISTEM INFORMASI PERSEDIAAN BARANG DENGAN METODE BUFFER STOK BERBASIS WEB - Kasih Purwantini; Munifah Munifah; Dewi Novita (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research was conducted based on the need for a system that can record inventory at PT Sumber Rejeki Semarang. PT Sumber Rejeki Taura is engaged in the water pump trade. The inventory management system currently running at PT. Sumber Rejeki Taura is manual management. In carrying out daily activities, PT Sumber Rejeki Taura still uses a manual inventory recording system. When making a report to the management, the inventory report is taken from the ledger, resulting in long recording because it has to work twice to record it in the book and make a report. If at any time the company owner wants to know and see the inventory of goods, it will take a long time because it has to be re-capitulated. Likewise, in searching for data, you have to check the data one by one, this takes time because in any case, recording in the book can cause various obstacles, such as data can be changed, for example, recording the inventory report is changed by someone else who is not responsible without the owner's knowledge so that the data can be known to outside parties, books can be damaged because the paper is often turned over when checking the inventory report, in addition, the inventory of goods that is currently running at PT Sumber Rejeki Taura has not been well designed, so far the inventory of goods at PT Sumber Rejeki Taura is only limited to recording in books and receipts. Seeing these problems, the author provides a proposed solution by designing a web-based inventory information system to help the performance of Toko Besi T employees or also called PT. Sumber Rejeki Taura Semarang in processing and storing data. The author will use Macromedia Dreamweaver and CSS software then supported by PHP and MySQL databases in the XAMPP Control Panel application.